2018
DOI: 10.3802/jgo.2018.29.e4
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis ofKRASand its clinical implications in cervical cancer patients

Abstract: ObjectiveThe predictive and prognostic role of KRAS mutations in cervical cancer remains inconclusive. The aim of this study was to explore the clinicopathological and prognostic relevance of KRAS mutations in invasive cervical cancers (ICC).MethodsReverse transcription polymerase chain reaction (PCR) and Sanger sequencing were employed to detect KRAS mutations in 876 ICC patients. Quantitative real-time PCR was used to detect human papillomavirus (HPV) 16 and HPV 18.ResultsNon-synonymous mutations of KRAS wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…Spaans et al [16] showed that KRAS mutations occurred more frequently in ACs than in SCCs, and Wright et al [12] indicated that KRAS mutations were detected only in ACs, but not in SCCs. Similar results were obtained in other studies [14,15,19], and these somatic mutations were commonly detected in both Caucasian and Asian cervical cancer patients. The frequency of TP53 mutations was higher in ACs than in other histological types.…”
Section: Discussionsupporting
confidence: 91%
“…Spaans et al [16] showed that KRAS mutations occurred more frequently in ACs than in SCCs, and Wright et al [12] indicated that KRAS mutations were detected only in ACs, but not in SCCs. Similar results were obtained in other studies [14,15,19], and these somatic mutations were commonly detected in both Caucasian and Asian cervical cancer patients. The frequency of TP53 mutations was higher in ACs than in other histological types.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in CC have elucidated either isolated somatic mutations or copy number alterations for several cancer-related genes, such as PIK3CA , PTEN , TP53 , STK11 and KRAS , and explored their clinical relevance 7 11 . In addition, for comprehensive elucidation of genetic alterations in cervical tumours, recurrent somatic mutations of MAPK1 , HLA-B , EP300 , FBXW7 , NFE2L2 , and ERBB2 in squamous cell carcinoma (SCC), as well as those of ELF3 and CBFB genes in adenocarcinoma (AC), have been identified using whole-exome sequencing analysis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for comprehensive elucidation of genetic alterations in cervical tumours, recurrent somatic mutations of MAPK1 , HLA-B , EP300 , FBXW7 , NFE2L2 , and ERBB2 in squamous cell carcinoma (SCC), as well as those of ELF3 and CBFB genes in adenocarcinoma (AC), have been identified using whole-exome sequencing analysis 12 . Some studies have reported that CC patients with mutant KRAS and PIK3CA have a poorer survival rate than those with wild-type 9 , 11 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The KRAS G12S mutation has been reported to occur in 4.9%-5.7% of colorectal cancer samples harboring mutations in the KRAS gene [44]. The KRAS A59T mutation has been detected in 24 tissue samples from the large intestine [44], stomach [45], salivary gland [46], lung [44], and cervix [47], of which 13 cases (54%) were identified in CRC [44]. The novel mutants KRAS Y137C (NM_004985.3: c. 410A>G; p.137Y>C) and NRAS A11V (NM_002524.5: c. 32C>T; p.11A>V) have not been previously reported to occur in CRC and as such, their functional impact and phenotypic consequences also remain unknown.…”
Section: Discussionmentioning
confidence: 99%